2011
DOI: 10.1097/01.naj.0000399310.83160.73
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Online Social Networking Patterns Among Adolescents, Young Adults, and Sexual Offenders

Abstract: The use of the Internet presents relatively new and complex issues related to the safety and privacy of adolescents and young adults, and it's crucial that our understanding keep pace with these changes. Possible nurse-initiated policy recommendations include designing technologies and educational programs to help in the identification of suspicious online behaviors; strengthening Internet filters and privacy options for protecting students online; and school outreach for students who are harassed, threatened,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
5
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 6 publications
3
36
5
7
Order By: Relevance
“…This percentage is comparable to recent work that also included the sending and receiving of explicit text messages in the operational definition of sexting. 7 However, this result is contrary to recent work that focused on the sending and receiving of naked photos. 5 Percentage disparities most likely reflect differences in sexting definitions and sample ages.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This percentage is comparable to recent work that also included the sending and receiving of explicit text messages in the operational definition of sexting. 7 However, this result is contrary to recent work that focused on the sending and receiving of naked photos. 5 Percentage disparities most likely reflect differences in sexting definitions and sample ages.…”
Section: Discussioncontrasting
confidence: 55%
“…This rate is somewhat higher than was found in other work 7 ; although the findings rely on perceptions of peer behavior and not necessarily observed behavior. Additionally, knowing someone who sexted was strongly associated with an individual' s own sexting behavior.…”
Section: Discussioncontrasting
confidence: 53%
“…Findings on gender differences, however, are inconclusive. While some studies reported no gender differences in sexting (Hinduja & Patchin, 2010;Lenhart, 2009), other studies found that more boys than girls send sexts (Baumgartner, Valkenburg, & Peter, 2010;de Graaf, Meijer, Poelman, & Vanwesenbeeck, 2005;Dowdell, Burgess, & Flores, 2011). Some few studies also reported that more girls than boys engage in sexting (Mitchell et al, 2012; The National Campaign to Prevent Teen and Unplanned Pregnancy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to potential solutions from the environment, few recommendations have been tested, but several have been suggested, including educational programs and individualized support (Dowdell, Burgess, & Flores, 2011;Holmes & O'Loughlin, 2014;Raghavendra et al, 2013). Also suggested are computerized, policybased or legal solutions designed to increase data and user security (Charlotte, 2010).…”
Section: Technical Dimensionmentioning
confidence: 99%